The ballad of songbirds and snakes - Collins, Suzanne (Scholastic Press, 2020)
Eighteen-year-old Coriolanus Snow has only one shot at earning the glory of becoming a mentor in the Hunger games and revive the reputation of the fallen house of Snow. However, his assignment is a humiliating one--he must try to make a champion of the female tribute from District 12, the lowest of all the districts, and the choices of Coriolanus will affect both his life, the life of the girl he is starting to fall for, and his whole world.